Energy absorption of thin-walled empty and foam-filled tubes - Fan, Zhihua (2013)
Recently, more attention has been paid to the energy absorption capability of novel structures. As one of the most versatile components in impact or blast protection, thin-walled tubes have been specifically explored by many researchers. Cellular materials, such as metallic foams, are used as impact energy absorbers in crash and blast protection because of their unique mechanical behavior. With this promising new material, the present project aims to develop energy-absorbing devices incorporating both thin-walled tubes and metallic foams. One of the methods for improving crashworthiness performance of the thin-walled tubes under axial crushing is to vary the cross-sectional shape with convex polygons. It is evident that severe deformation occurs near the corner of tubes and most of the number of corners in the cross-section affects the efficiency of energy absorption, to a large extent. As an alternative, it is also necessary to develop tubes with concave polygon sections by introducing the extra non-convex corners. Four types of geometries were studied experimentally and numerically, including hexagon, octagon, 12-sided and 16-sided star. The increase in the number of inward corners demonstrates a promising improvement in energy absorption, but to a certain extent. In addition, for a regular triangular tube, which is a polygon with an acute angle and odd number of sides, a new type of basic plastic collapse folding element is proposed based on the Finite Element Analysis (FEA) and cardboards. The theoretical collapse modes are validated against corresponding experiments. Furthermore, in order to explore the deformation behavior of the metallic foams, quantitative information is extracted on the state of stresses during the axisymmetric expansion of a cylindrical hole located at the center of an infinite block of metallic foam. A macroscopic phenomenological constitutive model of crushable foam is employed, considering the initial and subsequent yielding surfaces in the space of the effective stress and hydrostatic stress. Simulations are performed using finite element analysis and the results demonstrate a good agreement with the analytical solutions newly obtained. The evolutions of plastic zone during the expansion are discussed and a map is further obtained exhibiting the evolution of three deforming zones, i.e. elastic, plastic and densification of the foam.